Expectations over Big Data: The voice of higher education´s professors and students - López Núñez, Julio; Cerda-Neumann, Gerardo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Data has become a significant element in understanding the behavior of various systems. In this context, Big Data is a concept that refers to working with large volumes of data, with a blurred boundary between data analysis and data management. To this end, this research is framed in the qualitative paradigm through interviews with students and teachers participating in an introductory course on Big Data. It seeks to unveil the utility surrounding this topic. The main findings show a divergence between Big Data and what is understood of him.